2002
DOI: 10.1063/1.1428800
|View full text |Cite
|
Sign up to set email alerts
|

Direct detection of H atoms in the catalytic chemical vapor deposition of the SiH4/H2 system

Abstract: The absolute densities of H atoms produced in catalytic chemical vapor deposition (Cat-CVD or hot-wire CVD) processes were determined by employing two-photon laser-induced fluorescence and vacuum ultraviolet absorption techniques. The H-atom density in the gas phase increases exponentially with increases in the catalyzer temperature in the presence of pure H2. When the catalyzer temperature was 2200 K, the absolute density in the presence of 5.6 Pa of H2 (150 sccm in flow rate) was as high as 1.5×1014 cm−3 at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
124
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 158 publications
(136 citation statements)
references
References 46 publications
10
124
2
Order By: Relevance
“…H-atom ( ), O-atom ( ), and OH-radical ( ) densities calculated by the CHEMKIN software package. The preexponential factors for reactions (4) and (5) The OH-radical density obtained in the present system is higher than those obtained in the catalytic decomposition of H 2 /O 2 mixed systems [6,8]. However, that is less than those reported in plasma processes [32][33][34][35][36].…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…H-atom ( ), O-atom ( ), and OH-radical ( ) densities calculated by the CHEMKIN software package. The preexponential factors for reactions (4) and (5) The OH-radical density obtained in the present system is higher than those obtained in the catalytic decomposition of H 2 /O 2 mixed systems [6,8]. However, that is less than those reported in plasma processes [32][33][34][35][36].…”
Section: Discussioncontrasting
confidence: 50%
“…Since SiO x N y is less dense and more flexible compared to SiN x , that can be used as an interlayer to cover the microslits formed in SiN x films, which can be used as passivation films for organic light emitting diodes. The problem is that O 2 is reactive to SiH 4 , one of the most widely used source gases of silicon. The situation is similar when N 2 O is used as a source gas.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As for the pressure dependence of the photoresist removal rate, Hashimoto et al have reported that there is no H 2 pressure dependence between 67 and 200 Pa [11]. It should be noted that the H-atom density saturates against the H 2 pressure under such high pressure conditions [26] and that the H atoms produced may be completely thermalized before arriving at the substrate surfaces. In our past study, we reported that the removal rate increases with hydrogen pressure between 0.4 and 7.2 Pa [12].…”
Section: Introductionmentioning
confidence: 99%
“…8 LIB of silane ͑SiH 4 ͒ has been largely used in laser-induced chemical vapor deposition ͑CVD͒ and plasma-enhanced CVD for obtaining amorphous and hydrogenated silicon films. [9][10][11][12][13][14][15] Besides, higher silanes ͑disilane and trisilane͒, more effective in absorbing IR radiation, have been described as very suitable to act as precursors to a-Si: H films and from plasma decomposition induced by glow discharge. A major feature of these processes is a deposition rate enhancement of a factor of over 20 compared to monosilane.…”
Section: Introductionmentioning
confidence: 99%